CD Study of the G-Quadruplex Conformation - Kejnovská, Iva; Renčiuk, Daniel; Palacký, Jan; Vorlíčková, Michaela (Methods in molecular biology (Clifton, N.J.), 2019)
Circular Dichroic (CD) spectroscopy is one of the most frequently used methods for guanine quadruplex studies and in general for studies of conformational properties of nucleic acids. The reason is its high sensitivity to even slight changes in mutual orientation of absorbing bases of DNA. CD can reveal formation of particular structural DNA arrangements and can be used to search for the conditions stabilizing the structures, to follow the transitions between various structural states, to explore kinetics of their appearance, to determine thermodynamic parameters, and also to detect formation of higher order structures. CD spectroscopy is an important complementary technique to NMR spectroscopy and X-ray diffraction in quadruplex studies due to its sensitivity, easy manipulation of studied samples, and relative inexpensiveness. In this part, we present the protocol for the use of CD spectroscopy in the study of guanine quadruplexes, together with practical advice and cautions about various, particularly interpretation, difficulties.
Keywords: Circular dichroism spectroscopy; Magnetic Resonance Spectroscopy; Guanine-rich genomic sequences; konformace nukleové kyseliny; X-Ray Diffraction; G-kvadruplexy; cirkulární dichroismus; G-Quadruplexes; Nucleic Acid Conformation; DNA conformational transitions; Circular Dichroism; Guanine quadruplex; DNA; difrakce rentgenového záření; Interpretation of CD spectra; magnetická rezonanční spektroskopie